A jornada do herói Sérgio e dos outros meninos n’O Ateneu, de Raul Pompeia - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The course of Sérgio and the other boys in The Athenaeum, by Raul Pompeia, is the subject of the present research that investigates how the stages of formation of the hero are analogous to the journey experienced by students of realist romance by Pompeia, starting from the assumption of trajectory systematized by Joseph Campbell who proposes the course being expressed through the monomito whose nuclear structure comprises the phases of the hero 's trajectory, namely: separation - initiation - return. We perceive at the Athenaeum boarding school an environment of survival, deformation and dehumanization in which scenes of violence make up the trajectory of inmates in nineteenth-century Brazil (re-created through fiction). The school in Raul Pompeia's novel as an essential space in human formation (of the hero), the Athenaeum being the opposite of the environment of formation of heroes. The approach sought as theoretical foundation: the studies about European and Brazilian of Romance, Romanticism and Realism in Ian Watt, Antonio Candido and Alfredo Bosi; the trajectory and the transformations of the hero in Aristotle and Mikhail Bakhtin, highlighted here in Joseph Campbell; the theory of literary and cultural residuality, systematized by Roberto Pontes, and present in José William Craveiro Torres; the History of Mentalities in Jacques Le Goff and Georges Duby; the human formation in Erasmus of Rotterdam; the History of Education in Eliane Marta Teixeira Lopes, Luciano Mendes Faria Filho and Cynthia Greive Veiga.
Keywords: Literatura brasileira; Pompéia, Raul, 1863-1895. Ateneu; Realismo; Educação na literatura; LINGUÍSTICA, LETRAS E ARTES: LETRAS; Romance; Realismo; Trajetória do herói; Residualidade; O Ateneu; Raul Pompeia; Educação humana; Educação